Alive To God Studies In Spirituality - Packer, James Innell, 1926-; Wilkinson, Loren (Downers Grove,IL IVP, 1992)
Includes bibliographical references. Contributor's include J.I. Packer, Bruce K. Waltke, W.J. Dumbrell, Gordon D. Fee, John Stott, Thomas F. Torrance, James B. Torrance, Ian S. Rennie (Aspects of Christian Brethren spirituality), Walter L. Liefeld. F.F. Bruce was invited to contribute, declined for health reasons, and died shortly afterwards.
James Housten was from an Exclusive Brethren background, founder of Regent College, Vancouver, a Christian Brethren/Interdenominational college. This book was compiled as a gift for James Housten's 70th birthday, 1992.
Keywords: Housten, James MacIntosh, -- 1922-; Spirituality -- history